Pelatihan Pidato Bahasa Inggris untuk Anak-Anak Sekolah Dasar - Sudewi, Ni Ketut Putri Nila; Muhlisin (Jurnal Ilmiah Pengabdian dan Inovasi, 2023)
English Speech Training for elementary school children is a form of community service provided by Bumigora University. This community service activity was held for two months, from May 6, 2023, to June 30, 2023. The purpose of the community service program in the form of English speech training is to improve the public speaking skills of elementary school students in using English. There were some methods used, such as pre-test, early evaluation, orientation, drilling, and feedback. This program received tremendous enthusiasm from the students in the Kapitan environment; this can be seen from the enthusiasm and activeness of the students participating in this training activity. The outcomes of this training activity are an increase in the ability to pronounce words and sentences (pronunciation) and the confidence of the participants to speak or give speeches.